PENGARUH PENERAPAN ARTIFICIAL INTELLIGENCE DAN INTELEGENSIA TERHADAP PRODUKTIVITAS KERJA KARYAWAN DI BANK PEMBANGUNAN DAERAH (BPD) BALI - I Made Diatmika; Ni Luh Kardini; Ni Putu Yuli Trisna Dewi (Yayasan Nusantara Hasana Berdikari, 2024)
This study aims to determine the Effect of Implementation of Artificial Intelligence and Intelligence on Employee Productivity at Regional Development Bank (BPD) Bali. This research uses quantitative methods by distributing questionnaires to 93 respondents who are employees of the Regional Development Bank (BPD) Bali. The data analysis technique used is multiple linear regression analysis. The results showed that Artificial Intelligence has a tcount value = 1.764 with a significance value of 0.004 has a positive and significant effect on Employee Productivity. Intelligence has a tcount value = 11.471 with a significance value of 0.000 has a positive and significant effect on Employee Productivity. Simultaneously, Artificial Intelligence and Intelligence have a positive and significant effect on Employee Productivity.